Prophylactic heminephrectomy for an asymptomatic, non-functioning moiety in pediatric duplex systems: is cancer prevention justified? - Zhanghuang, Chenghao; Long, Na; Yan, Bing (Frontiers in Pediatrics, 2025)
BackgroundDuplication of the collecting system (DCS) is common. The management of asymptomatic, non-functioning moieties remains controversial because of a theoretical risk of malignancy, and prophylactic heminephrectomy is occasionally proposed despite the standard practice of reserving surgery for symptomatic complications.ObjectiveTo critically appraise whether current evidence supports prophylactic heminephrectomy solely for cancer prevention in asymptomatic pediatric duplex systems.MethodsWe conducted a focused narrative mini-review of PubMed (updated May 2025) and population-based cancer registries, concentrating on absolute malignancy risk and DCS-specific oncologic evidence.Evidence synthesisPediatric renal tumors are rare (Wilms tumor ≈7–10 per million children annually; pediatric renal cell carcinoma is even less frequent). The purported association between DCS and malignancy is based on six pediatric case reports (four Wilms tumors and two renal cell carcinomas). No denominator-based cohort data demonstrate an incidence above baseline. Mechanistic plausibility for carcinogenesis in a quiescent, uninfected, non-functioning moiety remains unproven. Although minimally invasive heminephrectomy is generally safe in experienced centers, complications such as bleeding, urinary leak, ureteral stump problems, and potential compromise of the preserved moiety are clinically relevant.ConclusionsCurrent evidence does not support routine prophylactic heminephrectomy for asymptomatic, non-functioning moieties in children. A conservative strategy with structured ultrasound surveillance at 6–12-month intervals and predefined surgical triggers is prudent and consistent with the available evidence.